PENGEMBANGAN MODEL PEMBELAJARAN GEOMETRI DENGAN PENDEKATAN KONSTRUKTIVISTIK - Wiwin Wiwin; Indri Astuti; Fadillah Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractAmong the fundamental things that become difficulties in understanding geometry is caused by the material geometry includes abstract things, rote so difficult to be understood by the students, thus requiring instructional media in the form of study guide in order to assist students in improving the learning process and learning outcomes especially on geometry material. This study aims to produce learning guide products in geometry learning, to produce the final product of tiered training module in geometry learning to describe the implementation of study guide book on geometry material and to describe geometry learning result by using study guide at Madrasah Ibtidaiyah Imaduddin Kubu Raya. This research is research of development of geoemetry learning model with constructivism approach of meggunakan development stage of Dic and Carey, with subject of research is class IV student with 24 student. Data were obtained through expert validation questionnaires, observations, interviews, student response questionnaires, and documentation. Further data analysis is done on the results of expert validation, observation, interview and questionnaire response learners. The results showed that the study guide can give a positive influence on the learning outcomes of geometry learning, this can be seen from the results after the learning process using the learning guide of 88.85% complete and 41.97% unfinished, so that the percentage of students progress in the process of learning geometry using learning panes. In addition, the increase can also be seen from the test results of two paired samples that show that the value of t arithmetic> t table (35.73> 1.711), means there are differences in learning results using learning guides in learning geometry. Thus the learning guide in the learning of geometry that has been done can help students to more easily study the material geometry. Key Words: Development of Model, Geometry, Constructivist Approach